THE INFLUENCE OF THE INDUSTRIAL REVOLUTION 4.0 ON EMPLOYEE PERFORMANCE IN NORTH CENTRAL TIMOR REGENCY WITH COMPETENCE AS A MEDIATION VARIABLE - Huda, Nurul; Baso, Budiman; Aziz, Syaefudin; Manane, Desmon Redikson (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2024)
The purpose of this research is to determine the effect of the industrial revolution 4.0 on employee competence in Timor Tengah Utara Regency, the effect of competence on employee performance in Timor Tengah Utara Regency, the effect of the 4.0 industrial revolution to employee performance in Timor Tengah Utara Regency, and the indirect effect of the 4.0 industrial revolution. To employee performance in Timor Tengah Utara Regency through Competence as a mediation variable. The method used in this study is quantitative with structural equation modeling (SEM) techniques. The number of samples used was 349 employees in North Central Timor Regency. The results of this research indicate that the industrial revolution 4.0 has a positive and significant effect on employee competence in Timor Tengah Utara Regency, Competence has a positive and significant effect to employee performance in Timor Tengah Utara Regency, the industrial revolution 4.0 has positive but not a significant effect on employee performance in Timor Tengah Utara Regency, and the industrial revolution 4.0 indirectly has a positive and significant effect to employee performance in Timor Tengah Utara Regency through Competence as a mediation variable.